2017
DOI: 10.1177/0046958017709103
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Differences Between Traditional Medicare and Medicare Advantage: A Risk-Adjusted Assessment Using Claims Data

Abstract: Medicare Advantage (MA) has grown rapidly since the Affordable Care Act; nearly one-third of Medicare beneficiaries now choose MA. An assessment of the comparative value of the 2 options is confounded by an apparent selection bias favoring MA, as reflected in mortality differences. Previous assessments have been hampered by lack of access to claims diagnosis data for the MA population. An indirect comparison of mortality as an outcome variable was conducted by modeling mortality on a traditional fee-for-servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Unlike previous research, which found a lower rate of mortality for people in a Medicare Advantage plan31, this study found a positive correlation between enrolment in an HMO for at least 6 of the 12 months prior to prediction and a statistically significant and higher risk of mortality. While not an indication of causation, one of several possible explanations for this correlation could be a higher likelihood of attention to resource utilisation and advanced directives in Medicare Advantage plans, and thus greater avoidance of aggressive end-of-life treatments.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike previous research, which found a lower rate of mortality for people in a Medicare Advantage plan31, this study found a positive correlation between enrolment in an HMO for at least 6 of the 12 months prior to prediction and a statistically significant and higher risk of mortality. While not an indication of causation, one of several possible explanations for this correlation could be a higher likelihood of attention to resource utilisation and advanced directives in Medicare Advantage plans, and thus greater avoidance of aggressive end-of-life treatments.…”
Section: Discussioncontrasting
confidence: 99%
“…Without these data, we do not know the underlying health status and comorbidity profile of patients with AKI requiring dialysis and patients requiring incident dialysis covered by private insurance, who have no insurance, or who receive care under Medicare Advantage. Studies in the general Medicare population suggest beneficiaries with Medicare Advantage typically have lower utilization and better outcomes than Fee-for-Service beneficiaries (24, 25), and a recent study reported that ESKD beneficiaries enrolled in Medicare Advantage Special Needs Plans had lower mortality and hospital utilization compared with ESKD Fee-for-Service beneficiaries (26).…”
Section: Discussionmentioning
confidence: 99%
“…The current literature does not sufficiently focus on assessing the appropriate number of additional procedures or diagnoses within a patient visit. Instead, the focus has been on developing risk-adjustment models concentrating on health outcomes [ 6 , 7 , 8 , 17 , 18 ]. These models do not address coding intensity.…”
Section: Introductionmentioning
confidence: 99%